Management Of Archives To Support Order Administration In Ujung Tanah’s Office Of Makassar City - Wahyudi Mokobombang; Abdul Azis; Muhammad Anas (Brilliant International Journal Of Management And Tourism, 2023)
The Ujung Tanah District Office's archive management has not gone as planned. The Ujung Tanah District Office does not yet have a dedicated archivist. This study's problem is the types of archives, the role of archives, organizing archives, archive storage systems, archive storage procedures, archive maintenance, archive security, equipment, archive equipment, and archive destruction, as well as the efforts made to overcome problems at the Ujung Tanah District Office in Makassar City. This study employs a qualitative approach. Researchers used interviews, observation, and documentation to collect data. The researcher's data analysis model employs the Miles and Huberman analysis model, in which the analysis is carried out continuously until a saturation point is reached. Based on indicators of the archive storage system, the process of storing and using archives, archive equipment and supplies, and archive depreciation, the results showed that the management of archives in the Ujung Tanah sub-district office in supporting administrative orders was carried out properly. The Ujung Tanah District Office's archive management faced several challenges, including a lack of archiving staff and inadequate knowledge of archives and archive storage facilities.